Analisis Faktor Yang Mempengaruhi Minat Mahasiswa Universitas Flores Dalam Memilih Lokasi Tempat Tinggal Kos : (Studi Kasus Kelurahan Paupire Kecamatan Ende Tengah, Kabupaten Ende) - Damianus Tola; Saveriana Juli (Ekspektasi: Jurnal Pendidikan Ekonomi, 2018)
Research results show that; (1) the influence of the environment on the interest of students of Flores University in choosing a place to live in boarding house can be seen that the value of t arithmetic on the environment variable is equal to 1.761 with a significance level of 0.004. Because the value of t count is greater than t table, namely (1.761)> (1.673) and its significance value (0.004) <(0.05) then it is said to be valid and fulfilling the requirements; (2) the effect of the price on the interest of Flores University students in choosing a boarding house location can be seen that the value of t count is greater than t table (2.317)> (1.673) and the significance value (0.022) <(0.05) is said to be valid and qualify; (3) the influence of facilities on the interest of Flores University students in choosing a boarding house location can be seen that the calculated value is greater than t table (1,691)> (1,673) and the significance value (0,007) <(0,05) is said to be valid and qualify; (4) the influence of decisions on the interest of Flores University students in choosing a place to live in boarding house can be seen that the value of t count is greater than t table (1.797)> (1.673) and its significance value (0.008) <(0.05).